EFL curriculum implementation in primary schools in South Sulawesi Province in Indonesia - Iskandar (Curtin University, 2014)
This mixed-methods study investigated South Sulawesi primary EFL teachers’ understanding of and attitudes towards the National Curriculum Framework (NCF), the basis of school curriculum development. It explored its influence on teachers’ teaching methods and the impact of EFL status as Local Content (LC) subject on their teaching. It revealed that teachers have an understanding of the NCF, most adhered to it, their methods complied with the recommended approach, and were aware of LC requirements.